Performance Comparison of the LPWAN Standards NB-IoT and LTE-M Based on Protocols and Message Volumes - Balbach, Samira; Dorn, Christian; Fraidling, Florens; Hagelauer, Amelie (2025 IEEE MTT-S Latin America Microwave Conference, LAMC 2025 - Proceedings, 2025)
The growing number of IoT devices necessitates sustainable hardware and software solutions. This work compares the power consumption of two low-power wireless communication boards, implementing the promising LPWAN standards NB-IoT and LTE-M with MQTT. The measurements assess the impact of the protocols on the overall energy efficiency. Subsequent research assessed the efficacy of data transmission strategies in the context of LPWAN systems, with a particular focus on the impact of message size and connection persistence on power efficiency. The findings indicated that strategic data aggregation and the maintenance of persistent connections enhance energy efficiency, guiding the development of more efficient IoT communication practices.
Created from Fastlane, Scopus look-up
Keywords: IoT; LPWAN; LTE-M; MQTT; NB-IoT